Learning spaces - Bligh, Brett; Crook, Charles (Springer, 2017)
Sociocultural accounts of education emphasise that learning occurs in and through mediated interactions with the world; technology in education mediated those interactions, and commonly strives to create distinctive experiences centred upon particular spaces. Yet, until relatively recently, most analyses have typically underemphasized those spatial aspects of how technology in education functions - how tools come to be used in particular spaces, intersect and challenge spatially embedded practices, and might be thereby designed "with space in mind". In this chapter, we set out some bases for a "spatial turn" in Technology Enhanced Learning (TEL) research. We argue that those of us working in that field need to better understand both technology and learning as spatial phenomena; that we must better conceptualise the design of technology and the spatial contexts of use; and that we should become more directly involved in designing and evaluating Learning Spaces themselves - thereby coming to view space as an integral part of the "technology" that might mediate learning. We emphasise the difficulties in conceiving how space and learning are related, and sketch six different models that view the development of spaces and learners as intertwined in increasingly complex ways. We conclude by considering some particular types of Learning Spaces and related issues such as apparent informality and flexibility; by considering pertinent directions in research on the design and evaluation of educational spaces; and by celebrating some of those strands of work within the TEL research field that do already strive to account for the spatial implications of technology.